Negotiating the Lome IV convention - Ramsaran, Ramesh F (Institute of International Relations Port of SpainTT, 1990)
Provides a brief background to the Lome Convention and presents an ACPapproach to the Lome IV negotiations. Summarises the ACP's main areas of concern regarding trade issues inter alia, access to Community Market; operation of the GSP and Uruguay Round; consultation procedures; preferential arrangements for agricultural production. Concludes that the effectiveness of Lome should begin with a critical review of the structure and functioning of Lome institutions.